PLASMA ANTITHROMBIN LEVELS OF PAKISTANI WOMEN WITH PRE-ECLAMPSIA - Rahmani, Muhammad Tariq Hamid; Tayyab, Muhammad; Tasneem, Tahira (Journal of Ayub Medical College Abbottabad, 1999)
Plasma antithrombin HI level/activity was determined in the gravid Pakistani women. Levels of AT III were significantly decreased in pre-eclamptic women compared to normal pregnant controls. The degree of reduction in plasma A T III level was correlated with the severity of the disease. In no instance was low plasma AT III associated with normal pregnancy. The relation of decreased AT III level may he valuable as a tool in diagnosing pre-eclampsia as a screening test/predictor, and as an indicator of severity of disease.